Measuring students’ loyalty through students’ perception of service quality: A case study at International College of Yayasan Melaka / Siti Aisah Ganti - Ganti, Siti Aisah (Bachelor of Science (Hons.) Statistics, 2015)
Service quality and students’ loyalty in the education institute is not contrary compared to other industry. Loyalty the industry requires customer to survive in the market while institution requires students to carry out their image. The specific objectives of the study was to investigate students’ perception of service quality that influences students’ loyalty and to examine whether tangible dimension (infrastructure) is the most dimensions of service quality that influences students’ loyalty. The sample size of the study consisted of 180 students belong to different program in International College of Yayasan Melaka (ICYM). The stratified sampling technique was used in order to select the representative samples. The study was analysed by structural equation modelling (SEM) with latest software, Analysis of Moment Structures (AMOS) program version 18.0. The results reveal that students’ perception of service quality has significant influences on students’ loyalty. However, tangible (infrastructure) dimension is not dimensions of service quality that influences students’ loyalty. Precisely, management and academic program are the dimensions of service quality that influence on students’ loyalty